2016
DOI: 10.1080/08927014.2016.1169402
|View full text |Cite
|
Sign up to set email alerts
|

The biofilm matrix ofCampylobacter jejunidetermined by fluorescence lectin-binding analysis

Abstract: Campylobacter jejuni is responsible for the most common bacterial foodborne gastroenteritis. Despite its fastidious growth, it can survive harsh conditions through biofilm formation. In this work, fluorescence lectin-binding analysis was used to determine the glycoconjugates present in the biofilm matrix of two well-described strains. Screening of 72 lectins revealed strain-specific patterns with six lectins interacting with the biofilm matrix of both strains. The most common sugar moiety contained galactose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Biofilm was stained simultaneously with fluorescent probes: Syto9 in green for cell detection and two fluorescently labeled lectins Concanavaline-A (ConA) in blue to detect a-D-mannosyl and a-D-glucosyl residues and wheat-germ agglutinin lectin (WGA) in red to detect N-acetylglucosamine (GlcNAc) residues. For details see Turonova et al (2016) (see also video S1) # Hana Turo nov a. Reuse not permitted. Delatolla et al, 2009;Hannig et al, 2010;Karcz et al, 2012;Pompilio et al, 2015).…”
Section: Microscopy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm was stained simultaneously with fluorescent probes: Syto9 in green for cell detection and two fluorescently labeled lectins Concanavaline-A (ConA) in blue to detect a-D-mannosyl and a-D-glucosyl residues and wheat-germ agglutinin lectin (WGA) in red to detect N-acetylglucosamine (GlcNAc) residues. For details see Turonova et al (2016) (see also video S1) # Hana Turo nov a. Reuse not permitted. Delatolla et al, 2009;Hannig et al, 2010;Karcz et al, 2012;Pompilio et al, 2015).…”
Section: Microscopy Methodsmentioning
confidence: 99%
“…Being noninvasive, CLSM represents the methods of choice for the distribution and in situ characterization analyses of EPS (Bhardwaj et al, 2013;Neu & Lawrence, 2014b;Watrous & Dorrestein, 2011). Identification of the EPS carbohydrates could be approached using fluorescence lectinbinding analysis (FLBA) which detects glycoconjugates and their distribution within the biofilm (Figure 10(C), and S1) (Marchal et al, 2011;Neu & Lawrence, 2014bTuronova et al, 2016;Zippel & Neu, 2011). Characterization of EPS carbohydrate using FLBA depends on the specificity of the lectins used (Weissbrodt et al, 2013;Zhang et al, 2015a).…”
Section: Measurement Of Eps Componentsmentioning
confidence: 99%
“…FLBA has been employed to study the matrix architecture in a variety of different biofilms, including environmental, industrial, and medical biofilms [1523]. After an initial screening step where the binding of a large number of fluorescently labeled lectins to a particular type of biofilm is tested, selected lectins exhibiting high affinity to the biofilms in question are employed to visualize and quantify specific glycoconjugate motifs [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that approximately 80% of bacterial infections are related to biofilm formation because these polymeric structures give them good protection against antibiotics, disinfectants, the host immune system, and stressful environmental conditions . The biofilm‐producing capacity of Salmonella and Campylobacter strains isolated from different sources in the food supply chain is well known . This is a cause for concern in the food industry owing to the major public health problem it represents.…”
Section: Introductionmentioning
confidence: 99%